1990
DOI: 10.1007/bf00370779
|View full text |Cite
|
Sign up to set email alerts
|

Charge movement and calcium currents in skeletal muscle fibers are enhanced by GTP?S

Abstract: G-proteins play several regulatory roles in the cell. They can modulate ionic channels directly or in association with second messengers. In skeletal muscle, G-proteins modulate the activity of calcium channels either by acting directly on the channel and/or through a cAMP-dependent phosphorylating mechanism. The activation of G-proteins by GTP gamma S can also induce force generation in skinned fibers. In this paper we studied the effect of GTP gamma S on charge movement and calcium currents (ICa) in rat and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…A control peptide in which the putative amphipathic helix was disrupted by replacing two isoleucine residues with proline had no effect on voltage-dependent channel potentiation. Stimulation of PKA is widely reported to increase skeletal muscle Ca2+ channel activity (32)(33)(34)(35)(36)(37)(38). Surprisingly, neither Ht 31 peptide alone nor Ht 31 peptide with PKA catalytic subunit was found to alter basal channel activity or its voltage dependence.…”
Section: Discussionmentioning
confidence: 99%
“…A control peptide in which the putative amphipathic helix was disrupted by replacing two isoleucine residues with proline had no effect on voltage-dependent channel potentiation. Stimulation of PKA is widely reported to increase skeletal muscle Ca2+ channel activity (32)(33)(34)(35)(36)(37)(38). Surprisingly, neither Ht 31 peptide alone nor Ht 31 peptide with PKA catalytic subunit was found to alter basal channel activity or its voltage dependence.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies on skinned fibers, however, GTP),S did not potentiate depolarization-induced release (85). In voltage-clamped cut fibers, GTP),S was reported to increase charge movement (49,101) and calcium current (49), but in other studies, it was reported to have no effect on charge movement (85). G proteins activate L-type (DHPR) calcium channels in other preparations via DHPR phosphorylation by cAMP-dependent protein kinase (57, 78), and via direct interaction with the channel (73, 136).…”
Section: Magnesium Ionsmentioning
confidence: 93%
“…Indeed, CGRP has been reported to phosphorylate DHPRs in intact muscle cells, most likely via PKA [115]. First, DHPRs phosphorylation by PKA up-regulates the L-type Ca 2+ current, but does not affect the corresponding charge movement [116], which is actually the trigger for VGCR. However, the following evidence argues against this possibility.…”
Section: Potential Mechanisms Underlying Cgrp Effects On Ec Couplingmentioning
confidence: 99%